Re Fuse: Place, material, nature - Hoffman, Warren (School of Architecture, Planning and Geomatics, 2024)
The project ‘Re-Fuse' is about the transformation of a site where the landscape through its history, specifically in the past 60 years of recorded information is a visual and physical spectacle of the environmental damage humankind has caused in the search of virgin materials (Mining) and burying of used materials (Landfill). Essentially the project is about an analysis of a site and its context and through this analysis identifying a position and a response in the potential utilization of architecture as a tool to aid in a positive social and environmental impact on the community and society at large. It's about understanding place in order to determine a future, by engaging with the local materials and the existential soils of the site, past and present to reform a connection to a landscape disconnected from nature. But importantly, remembering its industrial and extractive past that led to its current state, including the influence society had on its morphology through the use of existing and new infrastructure, encouraging social engagement with the land and materials, promoting scientific research and the awareness of the impacts of waste including its potential as a valuable material resource. Thus, the primary focus being that of waste management, with the reuse of an existing abandoned industrial warehouse, refurbished through the utilization of existing and implementation of new spatial interventions to form a material recovery and transformation centre that's sole focus is to limit landfill use by seeing waste as a raw material via the creation of new products, increasing a materials lifespan through reuse, upcycling or downcycling, with the intention to keep the materials within our production systems, limiting the use of new mined resources.